The impact of employee performance and community participation on solid waste management effectiveness in Bukittinggi City, Indonesia - Fajriatul Rahmi Annisa; Lanin Dasman; Pranata Mulya Nico (BIO Web of Conferences)
This study investigates the impact of employee performance and community participation on solid waste management effectiveness in Bukittinggi City, Indonesia. As medium- sized cities face increasing waste management challenges due to rapid urbanization, un- derstanding contributing factors becomes crucial. Employing a quantitative approach with purposive sampling, this research surveyed 400 respondents across 24 sub-districts in Bukittinggi. Multiple and simple linear regression analyses reveal significant influences of both employee performance and community participation on waste management effec- tiveness. Employee performance, particularly in loyalty, work achievement, and respon- sibility, correlates positively with improved waste collection and city cleanliness. Com- munity participation, especially through idea contribution, physical involvement, and en- vironmental awareness, significantly enhances recycling rates and waste reduction. The study identifies gaps in community involvement in decision-making and program eval- uation processes. These findings emphasize the necessity of an integrated approach to urban waste management, highlighting the importance of enhanced employee training and more inclusive community engagement strategies. This research contributes to the understanding of sustainable urban waste management practices in developing countries’ medium-sized cities, offering practical insights for policymakers and urban planners in optimizing waste management systems.